Pengembangan Media Pembelajaran Intraktif Berbasis Prezi pada Pembelajaran Bahasa Arab - Mufti Imam; Hikmawati Rahayu (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to (1) explore the application of Prezi as an interactive medium in Arabic language learning, (2) identify the steps involved in developing Prezi-based instructional media, and (3) analyze the advantages and disadvantages of using this media. The research method employed is library research, which involves collecting information and data through various literary sources such as books, journals, notes, magazines, other references, as well as previous relevant research findings. The results of the study indicate that Prezi is a highly effective tool in the Arabic learning process. It presents learning materials in a visually appealing and interactive manner through dynamic and well-structured presentations. One of its major strengths is its ability to deliver information in a non-linear format while actively engaging students in the learning process. However, several limitations were identified, including dependency on internet connectivity, a learning curve for first-time users, and the potential for distraction due to excessive animation if not used appropriately. Therefore, these limitations can be addressed by integrating Prezi with other supporting media to ensure the continuity and effectiveness of the learning process. Therefore, the use of Prezi as an interactive learning medium remains a promising alternative for enhancing the quality of Arabic language education.